Metabolic Reprogramming of Alloreactive T Cells Through TCR/MYC/mTORC1/E2F6 Signaling in aGvHD Patients - Pan, Zengkai; Huang, Aijie; He, Yang; Zhang, Zilu; Jiang, Chuanhe; Wang, Luxiang; Qing, Kai; Zhang, Sujiang; Wang, Jianmin; Hu, Xiaoxia (Frontiers in Immunology, 2022)
Acute graft-versus-host disease (aGvHD) is the most common complication after allogeneic hematopoietic stem cell transplantation (allo-HSCT) and significantly linked with morbidity and mortality. Although much work has been engaged to investigate aGvHD pathogenesis, the understanding of alloreactive T cell activation remains incomplete. To address this, we studied transcriptional activation of carbohydrate, nucleotide, TCA cycle, and amino acid metabolism of T cells before aGvHD onset by mining the GEO datasets. Glycolysis had the most extensive correlation with other activated metabolic sub-pathways. Through Pearson correlation analyses, we found glycolytic activation was positively correlated with activated CD4 memory T cell subset, T cell proliferation and migration. T cell receptor, mTORC1, MYC signaling pathways and E2F6 might be “master regulators” of glycolytic activity. aGvHD predictive model constructed by glycolytic genes (PFKP, ENO3 and GAPDH) through logistic regression showed high predictive and discriminative value. Furthermore, higher expressions of PFKP, ENO3 and GAPDH in alloreactive T cells were confirmed in our pre-aGvHD patient cohort. And the predictive value of the aGvHD risk model was also validated. In summary, our study demonstrated that glycolytic activation might play a pivotal function in alloreactive T cell activation before aGvHD onset and would be the potential target for aGvHD therapy.